Comparison of Risk Tolerances and Investment Decisions of Participation Bank Customers and Conventional Bank Customers - Hüseyin Burgazoğlu; Salih Ülev; Mervan Selçuk (Sosyal Ekonomik Araştırmalar Dergisi)
This study investigates the structure of financial risk tolerances and risk perceptions of participation and conventional bank customers. Our results show that conventional bank clients have a higher average in both overall risk tolerance and financial risk tolerance. This means that participation bank clients are more risk-averse. However, the basis of the participation account includes profit-loss sharing, namely, risk sharing. Therefore, participation account holders were expected to be more risk-taking investors. The results show the opposite and support the managers and employees of participation banks who claim that their customer portfolios are not ready to invest in riskier products such as mudaraba and musharakah.